EMERGENCY UROLOGIC IN PREGNANCY - Utami, Putu Surya (E-Jurnal Medika Udayana; vol 2 no 12 (2013):e-jurnal medika udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE A variety of anatomical and physiological changes occurring during pregnancy, which can affect any organ system. Urological problems in pregnancy represent a diagnostic and therapeutic challenge. Urinary tract symptoms in pregnant women comprise urinary tract infection, acute pyelonephritis, acute urinary retention, hematuria, placenta percreta, nefrolithiasis, uropathy obstructive, and malignancy urologic. A multidisciplinary approach is necessary, from the anesthetic and obstetric team. In this review, I will discuss the common urological problems that occur during pregnancy and outline an approach to their management. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:"Times New Roman";}
Keywords: pregnancy, urological, emergency